Uma faceta do vínculo entre o sentimento religioso e o sofrimento psíquico de Anne Frank, a partir do seu diário. - Bezerra, Luiz Carlos de Siqueira (2021)
The present research sought to reflect on the religious sentiment of the adolescent Anne Frank, in order to ascertain whether it was formed as a response to the helplessness suffered during the time, she lived in seclusion to escape Nazi persecution (1942-1944). Choosing Psychoanalysis as a theoretical framework, a study was developed in two chapters. In the first, we sought to understand the religious feeling in adolescents, developed from a literature review initiating from the Freudian considerations that religious feeling has its source in helplessness and is formed by nostalgia for the father. In the second, a qualitative analysis was carried out of the religious feeling of Anne Frank expressed in her diary, identifying expectations and fears suffered in her adolescent passage, lived in hiding, as well as the strengthening role of her religious feeling in coping with psychic suffering. The development of this study was made by following the chronological path of reports given in her diary, considering the psychic development of the adolescent and the verbs which are present inside the word "religare", which suggest the presence of three moments for religious feeling: connect, disconnect, and reconnect. From Psychoanalytical Theory, conceptual notions were identified and selected, which were presented and associated with the reports, testimonies and narratives selected for study. The testimonial work researched reveals that Anne is experiencing an adolescent crisis aggravated by persecution and the fear of being captured and killed. It was found that the diarist Anne Frank demonstrated being supported by her religious feeling, in her dialogue with God, and to have been strengthened by writing of her diary, whose addressee is an imaginary friend. The relevance of the production of writing in an intimate diary is also affirmed as a facilitator of adolescent elaborations, since it promotes a dialogical field in which the writer dialogues with the other of themselves, within themselves. The discoveries found in this dissertation enabled a better understanding of the articulation between the typical conflicts of adolescence and the religious dimension experienced in this period.